2020
DOI: 10.3390/jcm9103061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Instrument Design and Technique on the Precision and Accuracy of Objective Refraction Measurement

Abstract: Background: To evaluate the precision and accuracy of objective refraction measurement obtained with combinations of instrument design and technique. We also compared the performance of the instruments with subjective refraction measurements. Method and analysis: The objective refraction was measured in 71 subjects with three autorefractometers that have different designs and measurement principles (binocular with fogging, binocular without fogging, and monocular with fogging). Repeatability and reproducibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(36 reference statements)
1
10
0
Order By: Relevance
“… 21 , 22 Repeatability also reflects the measurement technique's ability to discriminate one value of the given parameter from another – the higher the precision, the better the discriminant capability. 21 , 22 Although reports of accuracy and repeatability of autorefractors are available aplenty in the literature, 17 , 19 , 20 , 23 25 a systematic, comparative analyses of accuracy and repeatability across different autorefraction techniques obtained from the same cohort of subjects is not as readily available. Such an analysis will provide critical input on one technique's relative performance against others, enabling evidence-based justification of their utility as a starting point for subjective refraction in the clinic and as a screening tool for refractive errors in public health settings.…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 Repeatability also reflects the measurement technique's ability to discriminate one value of the given parameter from another – the higher the precision, the better the discriminant capability. 21 , 22 Although reports of accuracy and repeatability of autorefractors are available aplenty in the literature, 17 , 19 , 20 , 23 25 a systematic, comparative analyses of accuracy and repeatability across different autorefraction techniques obtained from the same cohort of subjects is not as readily available. Such an analysis will provide critical input on one technique's relative performance against others, enabling evidence-based justification of their utility as a starting point for subjective refraction in the clinic and as a screening tool for refractive errors in public health settings.…”
Section: Introductionmentioning
confidence: 99%
“…We performed this measurement and waited 2 minutes to repeat it again. The previous autorefractor precision studies have analyzed the repeatability with either 2 or 3 repeated measurements [ 10 , 11 , 30 , 32 , 33 ]. As a supplementary evaluation to assess how the repeatability varies with 3 repeated measurements, we evaluated one of the autorefractor (NIII) on a subset of 16 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The pupil zone used for refraction measurement is also different in these methods. Previous studies have shown the objective refraction measurements obtained with different autorefractors vary, and it is suggested that this variation could be due to the measurement principle and design of each instrument [10][11][12][13][14]. The autorefractors are available as tabletop or handheld, and the clinical studies have shown that on average the differences among these two types of autorefractors are not clinically significant [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…As observed by Pei et al, 17 cycloplegic measurements are generally more positive or less negative than refractions without cycloplegia. Although enough fogging and standardized operations were performed to minimize the influences induced by accommodation, 31 this may not be enough for individuals with hyperopia or under the age of 10 years. 32 Hence, we urge caution and prudence when conducting tele-controlled subjective refraction on those patients.…”
Section: Discussionmentioning
confidence: 99%